Training Of 'Aisyiyah Cadres In Participation Of Early Detection Of Non-Communicable Diseases Through Posbindu Activities - Fatikhah, Fatikhah; Munawaroh, Siti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Non-communicable diseases (NCDs) are a burden for society in general and become a heavy burden for the Indonesian people, because NCDs are diseases that will be experienced by a person for a life time. One of the policies in controlling NCDs that is effective and efficient is empowerment and increasing community participation. The involvement of women's organizations is one of the activity to help government programs to prevent NCDs. One of them is Aisyiya. Methods: Community service activities implemented on September, October and November 2021. The focus of this activity is to increase the participation of Aisyiyah cadres in Posbindu activities. The process of this activity includes providing materials to increase understanding of NCDs early detection efforts through Posbindu activities, being trained to improve skills, as well as assistance in implementing activities. Activity results: Early detection of NCDs in implementation includes checking height, weight, blood pressure, blood sugar, cholesterol and uric acid. The results of the implementation, found many non-communicable diseases in the community, namely hypertension 31%, the incidence of Diabetes Mellitus, 6% and pre-DM 19%. Uric acid 26%, cholesterol 24%. These results illustrate the need for Posbindu cadres to detect NCDs early. Conclusion Cadres have the ability to detect risk factors and many people who are detected are at risk of developing NCDs. This activity went smoothly, the cadres were very enthusiastic to apply these skills in NCDs risk factor detection activities.